2014
DOI: 10.1186/1751-0147-56-19
|View full text |Cite
|
Sign up to set email alerts
|

A serological study of canine herpesvirus-1 infection in a population of breeding bitches in Norway

Abstract: BackgroundCanine herpesvirus-1 (CHV1) causes a fatal hemorrhagic disease in neonatal puppies and is associated with infertility in female dogs. This study was conducted to assess the status of CHV1 infection in bitches in proestrus or estrus and to investigate possible risk factors by a detailed questionnaire. Blood samples were collected from healthy bitches (n = 193) not vaccinated against CHV1, aged one year or older and admitted for estrus control to the Canine Reproductive Clinical Unit, Norwegian School … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…CaHV-1 infection was found in puppies originating from most areas of Denmark and puppies of different breeds were affected. Although it is difficult to extrapolate from a study based on examination of 57 dead puppies from 37 litters to the Danish dog population in general, these findings still indicate that CaHV-1 occurs widely in the Danish dog population similarly as previously reported from other North European dog populations [ 14 - 18 ]. The overall prevalence of CaHV-1 infection in this study was 22.8%, but it varied between age groups.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…CaHV-1 infection was found in puppies originating from most areas of Denmark and puppies of different breeds were affected. Although it is difficult to extrapolate from a study based on examination of 57 dead puppies from 37 litters to the Danish dog population in general, these findings still indicate that CaHV-1 occurs widely in the Danish dog population similarly as previously reported from other North European dog populations [ 14 - 18 ]. The overall prevalence of CaHV-1 infection in this study was 22.8%, but it varied between age groups.…”
Section: Discussionmentioning
confidence: 62%
“…Other studies have identified bacterial infections and fetal asphyxia as the main causes of puppy mortality [ 11 , 12 ]. Reports of fatal neonatal CaHV-1 infections have been published [ 13 , 14 ] and even though serological studies from many European countries indicate that CaHV-1 infection is widespread in adult dogs, with antibody prevalence ranging from 40-88% [ 14 - 18 ] CaHV-1 is not considered to be a major cause of mortality in puppies [ 10 - 12 ]. However, information on the prevalence of CaHV-1 infection in neonatal dogs is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the titres that we found in our study suggests that the virus circulates in the kennels and that high titres may be a consequence of frequent reactivation and reinfection. Stress factors can reactivate a latent infection, and oestrus itself is a potential stressor: 85.5% of breeding bitches in proestrus or oestrus were classified as CHV-1 positive in a survey in Norway [12]. CHV-1 is considered to be poorly immunogenic, and antibodies raised against the virus after infection generally decline within a two-month period [6], although low titres can persist for up to eight months or longer [13].…”
Section: Discussionmentioning
confidence: 99%
“…Dahlbom et al (2009) also reported 81.5% seroprevalence of CHV-1 in Finland [11]. Furthermore, the seroprevalence of CHV-1 infection was determined as 85.5% by immunoperoxidase monolayer assay (IPMA) in Norway [20]. Similarly, in a study performed in turkey in which virus neutralization test (VNT) and ELISA were used for investigation of CHV-1 seroprevalence, antibody against CHV-1 was detected in 39.3% of samples by ELISA in comparison to 29.4% of the specimens using VNT [21].…”
Section: Discussionmentioning
confidence: 97%